Automatic number priming effects in adults with and without mathematical learning disabilities - Defever, Emmy; Goebel, Silke M.; GHESQUIERE, Pol; Reynvoet, Bert (Frontiers in Psychology, 2014)
This study examined automatic number processing in adults with mathematical learning disabilities (MLD). The performance of adults with MLD during an automatic symbolic and non-symbolic priming task was compared to gender-, age- and IQ matched controls. No difference in the priming distance effect was found between the adults with and without MLD, suggesting that adults with MLD have an intact magnitude representation. Moreover, the adults with MLD did not have problems in processing the numerical symbols 1-9, suggesting that this basic deficit which is experienced by children with MLD is resolved by adulthood.